Nobody Expects the Spanish Inquisition: Cultural Contexts in Monty Python - Dobrogoszcz, Tomasz (Rowman & Littlefield Publishers, 2014)
Monty Python’s Flying Circus was one of the most important and influential cultural phenomena of the 1970s. The British program was followed by albums, stage appearances, and several films, including Monty Python and the Holy Grail, Life of Brian,and Monty Python’s The Meaning of Life. In all, the comic troupe drew on a variety of cultural references that prominently figured in their sketches, and they tackled weighty matters that nonetheless amused their audiences. In Nobody Expects the Spanish Inquisition:Cultural Contexts in Monty Python, Tomasz Dobrogoszcz presents essays that explore the various touchstones in the television show and subsequent films. These essays look at a variety of themes prompted by the comic geniuses: Death The depiction of women Shakespearean influences British and American cultural representations Reactions from foreign viewers This volume offers a distinguished discussion of Monty Python’s oeuvre, exhibiting highly varied approaches from a number of perspectives, including gender studies, post-structuralism, psychoanalysis, and cultural studies. Featuring a foreword by Python alum Terry Jones, Nobody Expects the Spanish Inquisition will appeal to anyone interested in cultural history and media studies, as well as the general fans of Monty Python who want to know more about the impact of this groundbreaking group.